PSIKOEDUKASI MENGOPTIMALKAN KECERDASAN EMOSI DAN SPIRITUAL ANAK SEJAK DINI - Khairul Amri; Nor Mita Ika Saputri; Sukatno Sukatno; Abubakar Abubakar (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2017)
Psychoeducation is a counselling on how to optimize the emotional intelligence and spiritual intelligence of children from an early age. This devotion is done for two months from January to February 2017. This dedication will be useful for teachers to develop children's intelligence optimally. Thus, teachers focus not only on the values of intellectual intelligence but also on other intelligence that will support the success of children later, such as emotional and spiritual intelligence. The results of this psychoeducation activity are: (1) the target of the previously planned trainees is at least 50 people, and the attendance is 100 people. Thus the target of the trainees can be said successful; (2) the teacher canrecognize and develop the child's emotional and spiritual intelligence through his body language; (3) the material delivered also has reached the target. The material presented includes: (a) recognizing the emotions of the child, (b) releasing negative emotions, (c) managing oneself emotions, (d) motivating oneself, (e) recognizing the emotions of others, (f) motivating others, (g) fostering relationships, (h) recognize the personality and emotions of the child, (i) adopt a parenting pattern appropriate to the child's development and personality, (j) communicate well with the child, (k) discuss all issues together, (l) tell grand stories, (m) involve the child in religious rituals.Keywords: Psychoeducation, emotional intelligence, spiritual intelligence